2017
DOI: 10.1124/jpet.117.244244
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ibuprofen on Skeletal Muscle of Dysferlin-Null Mice

Abstract: Ibuprofen, a nonsteroidal anti-inflammatory drug, and nitric oxide (NO) donors have been reported to reduce the severity of muscular dystrophies in mice associated with the absence of dystrophin or -sarcoglycan, but their effects on mice that are dystrophic due to the absence of dysferlin have not been examined. We have tested ibuprofen, as well as isosorbide dinitrate (ISDN), a NO donor, to learn whether used alone or together they protect dysferlin-null muscle in A/J mice from large strain injury (LSI) induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
2
2
0
Order By: Relevance
“…Active sites of muscle necrosis and bulk inflammation in both muscle groups was minor (<10%; S2B Fig ), yet reduced in rectus femoris muscles of HFD-fed mice. Despite obvious histological changes, plasma CK levels (a bi-phasic marker of muscle damage) were unaffected ( S2C Fig ), as published by others in dysferlin-null animals [25]. Together, these data show an exacerbation of muscle wasting by losartan in both the triceps brachii and quadriceps (rectus femoris), two muscle groups severely affected by LGMD2B [8,9].…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Active sites of muscle necrosis and bulk inflammation in both muscle groups was minor (<10%; S2B Fig ), yet reduced in rectus femoris muscles of HFD-fed mice. Despite obvious histological changes, plasma CK levels (a bi-phasic marker of muscle damage) were unaffected ( S2C Fig ), as published by others in dysferlin-null animals [25]. Together, these data show an exacerbation of muscle wasting by losartan in both the triceps brachii and quadriceps (rectus femoris), two muscle groups severely affected by LGMD2B [8,9].…”
Section: Resultssupporting
confidence: 79%
“…Based on the dramatic changes in muscle size in losartan-treated animals, one can anticipate changes in muscle weights; however plasma CK (a commonly used marker of muscle damage in both clinical and preclinical muscle disease) was not affected in the present study, as shown by others [25]. In mdx mice, reduced plasma CK and improved lipid profiles (reduced TG, increased HDL-C) were correlated with reduced muscle damage and pathology following chronic losartan treatment [13].…”
Section: Discussionsupporting
confidence: 55%
“…There are many examples in the literature that the severity of disease could be affected by genetic backgrounds and/or species. For example, mdx mice, a widely used mouse model of Duchenne muscular dystrophy (DMD), have much milder pathology as compared with DMD patients 20 ; the severity of muscular dystrophy in dysferlin-null mice depends on their genetic background 21 ; a common disease-associated missense mutation in α-sarcoglycan fails to cause muscular dystrophy in mice 22 . Studies have shown that genetic modifiers may affect the disease outcomes in DMD and dysferlinopathy 23 , 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Male C57Bl/6J mice (age of ~12 weeks at the start of the study) were purchased from Charles River (Sulzfeld, Germany): 32 total, 8 mice per group. This mouse strain was selected because there are a relatively large number of studies on ibuprofen in C57Bl/6J mice and therefore it is easier to choose relevant ibuprofen doses [35,36]. The choice of gender was based on the suggestion that men appear to be more affected by COVID-19 than women [37][38][39].…”
Section: Animal Study 451 Test Animalsmentioning
confidence: 99%